Fire response of a 3D multi-storey building with buckling restrained braces - Talebi, Elnaz (Brazilian Association of Computational Mechanics, 2015)
This paper investigates the performance of a three-dimensional multi-storey structure with Buckling Restrained Brace system (BRBs) under fire condition, using a sequentially coupled nonlinear thermal stress analysis. Efficiency of using BRBs in enhancing the strength and stiffness of a structural frame is compared with that of Ordinary Concentrically Bracing system (OCBs) under various fire scenarios. The proposed numerical model is verified by a series of full-scale fire tests carried out on an 8-storey structure at Cardington. The results indicate that the vertical movement of heated (buckled) column in the structural frame with BRBs is lesser than that with OCBs. Consequently, the tensile force and bending moment of the beam adjacent to the buckled column in the former is lesser than the latter. Also, BRB elements can perform better in redistributing the load sustained by heated columns without any buckling occurrence in the bracing member, in comparisons to the ordinary system. In general, it is observed that BRBs manifest an improved performance in re-stabilization of structural frame against fire for a longer period of heating time, such that a better fire resistance is offered to the whole building as compared to OCBs, due to a higher restraint provided onto the structure